(3GdeYJdj aj JYOO UhQ Gdhdjs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3bGd LdGd GdSjhWj GdTGaYjeMeO hBdg Yf QLd Mda HGdWdGb Cf hdj Gddg GdTjN YHO GdbGOQ GdWMWhWj HGJ YfOg aj GddjdI GdadGfjI aMda QLd BNQ HGdWdGb Cfg HGJ YfOg aj Jdc GddjdIs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3ajWjd GdacQ ajgG hjHPd GdeLghO aj MdgG hdG jfMd dg TjA efgG abGd acfJ Ydi bHQ TjNj GdTjN JGL GdOjf hCJhLgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1732s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs